Enhanced oral delivery of risperidone through a novel self-nanoemulsifying powder (SNEP) formulations: in-vitro and ex-vivo assessment. (17th August 2016) - Bandi, Srikanth; Sanka, Krishna; Bakshi, Vasudha
Abstract: Context: The oral delivery of risperidone encounters a number of problems, such as pH dependent solubility and low bioavailability, due to its lipophilicity and aqueous insolubility. Objective: To improve the solubility, dissolution and intestinal permeation thereby bioavailability of risperidone through a novel self-nanoemulsifying powder (SNEP) formulations. Materials and methods: Oleic acid, Tween ® 20, PEG 600 and Aerosil ® 200 were chosen as oil, surfactant, co-surfactant and carrier, respectively from solubility and emulsification studies. Ternary phase diagram was constructed to determine emulsifying region. Results and discussion: The Z-average and polydispersity Index of developed formulation was 83.1 nm and 0.306, respectively. Ex vivo permeation studies on isolated rat intestine indicated that the amount of risperidone permeated from SNEP formulation was increased around 4- and 1.8-fold than that of pure drug and marketed formulation, respectively. Conclusion: This developed SNEP formulations can be regarded as novel and commercially feasible alternative to the current risperidone formulations.